The Impact of Tony’s Existence to Donald’s Character Development in Green Book Movie - Rama Gunawan Sitinjak; Atrinawati Atrinawati (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
Peter Farelly’s Green Book is a fascinating biographical movie. This movie displays Donald’s personality development through his ego during his journey with Tony. It is the reason the writer interested to analyze the movie. This study is intended to describe the development of Donald’s ego. In order to describe the development, the writer practices close viewing. In his analysis, the writer uses the contextual method and psychoanalytic theory. The analysis shows that Donald’s superego experiences new vision. The result shows positive impact of Tony’s influence in breaking the doctor’s idealist temperament. This movie is good for general viewing, especially students of English Department studying the concept of psychoanalysis in practice.Keywords: idealist temperament; personality development; psychoanalysis; id ego, and superego